The Effect of Complaint Handling on Customer Loyalty Mediated by Customer Satisfaction: Exploring the Role of Customer Characteristics as a Moderating Variable - Deviana Astika Sari; Gusti Noorlitaria Achmad; Doddy Adhimursandi (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2026)
Indonesia has become one of the largest online transportation markets, with Grab facing increasingly intense competition from platforms such as Gojek and Maxim. Along with the rapid growth of service usage, customer complaints related to driver behavior, fare discrepancies, and service inconsistency have also increased, making effective complaint handling a critical factor in maintaining customer loyalty. Therefore, this study aims to examine the effect of complaint handling on customer loyalty, with customer satisfaction as a mediating variable and customer characteristics as moderating variables. This research employed a quantitative approach using purposive sampling of 150 Grab users in Indonesia who had experienced service-related complaints within the past 6–12 months. Data were collected through a structured questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The findings indicate that complaint handling has a positive and significant effect on customer satisfaction and customer loyalty. Customer satisfaction significantly mediates the relationship between complaint handling and loyalty, while customer characteristics, particularly age, education, and income, significantly moderate the relationship between satisfaction and loyalty. These findings highlight the strategic role of complaint handling in strengthening long-term customer loyalty in the online transportation industry.